Effects of soil and climatic factors on arbuscular mycorrhizal fungi in rhizosphere soil under Robinia pseudoacacia in the Loess Plateau, China. (29th September 2016) - He, F.; Tang, M.; Zhong, S. L.; Yang, R.; Huang, L.; Zhang, H. Q.
Abstract : We explored arbuscular mycorrhizal fungi (AMF) in the rhizosphere soil under Robinia pseudoacacia L., Leguminosae (black locust), and evaluated the relations between their diversity and soil and climatic factors in the semi‐arid Loess Plateau of northwest China. A total of 23 AMF species were identified at six sites. Of these, six belonged to the genus Funneliformis (Glomeraceae), five to Rhizophagus (Glomeraceae), three to Glomus (Glomeraceae), two to Acaulospora (Acaulosporaceae), two to Claroideoglomus (Claroideoglomeraceae), two to Septoglomus (Glomeraceae), one to Ambispora (Ambisporaceae), one to Scutellospora (Gigasporaceae) and one to Sclerocystis (Glomeraceae). The species that occurred in the largest proportion of soil samples were Rhizophagus intraradices (75%) and Funneliformis dimorphicum (66.7%). Soil‐available potassium was positively correlated with mycorrhizal colonization and species richness. Spore density was negatively correlated with soil pH, whereas the Shannon–Wiener diversity index was positively correlated with total potassium. Most of the soil and climatic factors measured affected the AMF indices directly rather than indirectly. The relative abundances of 13 AMF species were strongly affected by precipitation, temperature, total nitrogen, ammonium nitrogen and available potassium. This suggests that AMF species are diverse and Funneliformis was the most common and dominant AMF genus in the rhizosphere soil under black locust in the Loess Plateau. Precipitation directly affected AMF status and diversity in this distinctive semi‐arid ecosystem. Highlights: Analysis of the effects of soil and climatic factors on mycorrhizal colonization and AMF diversity of black locust. Improved understanding of AMF communities and their function in soil under black locust. Precipitation was the strongest direct factor that affected AMF in the semi‐arid region. Funneliformis was the most common AMF genus in rhizosphere soil under black locust.